Influence of multiple sclerosis on dynamic gait stability. (9th June 2020) - Lin, Meng-Wei; Liu, Wei; Yang, Feng
Abstract: Falls are a serious health threat for people with multiple sclerosis (MS). Dynamic gait stability has been identified as a key risk factor of falls. The development of effective interventions for preventing falls requires a sound understanding of how MS affects dynamic gait stability. The purpose of the study was to compare dynamic gait stability within the framework of Feasible Stability Region between people with and without MS during level walking at a self-selected speed. Twenty adults with MS and 25 age- and sex-matched healthy individuals were recruited. Dynamic gait stability at touchdown and liftoff on both the strong and weak sides was assessed as the primary outcome measurement. Spatiotemporal gait parameters, including step times, step length, step frequency, and foot landing angle, were determined as explanatory variables. People with MS exhibited lower stability at both gait events bilaterally than their healthy counterparts. The lower stability was mainly attributable to the slower gait speed in MS than in the healthy control. To compensate for the dynamic gait stability deficit resulting from the slow gait speed, individuals with MS adopted a short step length to shift the center of mass motion state closer to the feasible stability region. For people with MS, the stability value was higher on the weak side than on the strong side at touchdown, but not liftoff. The findings from this study could provide insight into the impact of MS on the control of dynamic gait stability.